Desenvolvimento de metodologias analíticas de metilação destinadas a produção de biodiesel e determinação de ácidos graxos em alimentos - Santos Júnior, Oscar de Oliveira (2013)
For the production of methyl esters in food or biodiesel analysis, the transesterification reaction is the most used. However, certain parameters must be controlled to obtain maximum performance. In this context, this project aimed to develop analytical methods for maximize yield of biodiesel and fatty acid composition of fish oil and to quantify the results in fatty acid mg g - 1 total lipids. Moreover, to evaluate the quality of the produced biodiesel through analyzes of total esters and triacylglycerol content, diacylglycerol, monoacylglycerol and free glycerol were done. Before starting the development of analytical methods, first we evaluated the yield of methylation reactions by acid and alkaline catalysis (Chapter II). Alkaline catalysis was chosen to optimize the mass yield of biodiesel from soybean oil (Chapter III), and acid catalysis was selected to optimize the yield of reaction for analysis of esters in foods. Reagents of analytical grade were used in all experiments. In the third and fourth chapters, the program design expert to optimize the best conditions of analysis for developing method was used. In the third chapter the variables used were the reaction time, catalyst(NaOH/methanol) concentration, molar ratio oil: methanol and reaction temperature. While, in fourth chapter the employed variables were reaction time and catalyst volume, and the energy source used for the experiment was radiation frequency ultrasound, 42 KHz. The analytical methodology developed in this fourth chapter, was satisfactory, since it is efficient for determination of different classes of fatty acids such as saturated, monounsaturated and polyunsaturated. Thus, it can be concluded that this methodology was satisfactory for the analysis of fatty acids in foods.